Effects of Automotive Test Parameters on Dry Friction Fiber-Reinforced Clutch Facing Surface Microgeometry and Wear - Roland Biczó (MDPI AG, 2021)
Wear and surface microgeometry aspects of fiber-reinforced hybrid composite dry friction clutch facings are revealed in a novel way: after different, real life automotive tests during their lifetime. This study examines and reveals the tribological response of friction material surfaces to real life application conditions with two different facing diameters and in two directions. Along the increasing activation energy scale, wear values increased according to two different trends, sorting tests into two main groups, namely ‘clutch killer’ and ‘moderate’. Wear results also highlighted the influence of mileage and test conditions, with clutch killer tests also creating considerable wear-more than 0.1 mm-at inner diameters: 1% higher wear was generated by 90% higher mileage; another 1% increment could be caused by insufficient cooling time or test bench-specific conditions. Surface roughness values trends varied accordingly with exceptions revealing effects of facing size, friction diameter and directions and test conditions: small (S) facings produced significantly decreased Rmax roughness, while large (L) and medium (M) size facings had increased roughness values; Rmax results showed the highest deviations among roughness values in radial direction; tests run with trailer and among city conditions resulted in more than 2% thickness loss and a 40–50% roughness decrease.